COLOR AND CRISPNESS ASSESSMENT OF FORTY POTATO VARIETIES FOR PROCESSING INDUSTRY OF BANGLADESH - Rahman, Md. Mahfuzar (Potato Journal, 2016)
Color and crispness may affect the processing quality of potato. Forty potato varieties grown in Bangladesh conditions were evaluated for skin color, flesh color, crispness and color of chips. All parameter studied in this experiment varied significantly among the different varieties. Among the forty varieties, twenty one varieties exhibited more than 55 L* value in skin color. In case of flesh color, ‘Lady Rosetta’, ‘Elgar’, ‘Multa’, ‘Amanda’ and ‘Ludmila’ showed higher than 75 L* value. The chips of ‘BARI TPS-1’ had the highest L* value (77.51) whereas the lowest value (53.54) was observed in ‘Multa’. ‘Almerah’ was characterized by a higher a* value (11.13) whereas the lowest value (-4.80) was observed in ‘Ailsa’. ‘Granola’ demonstrated maximum b* values (39.96) and lowest value (18.52) was observed in ‘Multa’. The chroma of ‘Granola’ (39.97) was the highest and lowest was exhibited in ‘Multa’ (18.55). It was observed that ‘Meridian’ (1.56), ‘Quincy’ (1.55) and ‘Granola’ (1.55) had the highest hue angle with no significant different, while the minimum value for hue angle was noted for ‘Caruso’ (-1.56), ‘Omega’ (-1.55) and ‘Forza’ (-1.54) with no significant different. ‘Ludmila’ (4.56 N) had higher crispness whereas; the minimum (0.16 N) was recorded from the variety ‘Quincy’ followed by ‘Meridian’ (0.23 N) and ‘Patrones’ (0.23 N).The variety ‘Lady Rosetta’, ‘Dheera’, ‘Cardinal’, ‘Ailsa’, ‘Tomensa’, ‘Caruso’, ‘Forza’, ‘Amanda’, ‘Ludmila’ and ‘Omega’ were found to be optimum chips color (L*, a*, b*, chroma, hue angle) and crispness compared to those of other varieties.